A new bathyal Fasciolaria (Mollusca: Caenogastropoda) from the southwestern Caribbean - de Souza, Paulino J.s. (Zootaxa, 2002)
A new bathyal species of Fasciolaria is described for the southwestern Caribbean based on conchological characters. Fasciolaria tephrina sp. nov. is distinguishable from its west Atlantic congeners by its ashen white color, highly convex whorls, long thin siphonal canal, and large deviated protoconch.